STRATEGI INDONESIA DALAM MEWUJUDKAN AOIP (ASEAN OUTLOOK ON INDO PASIFIC) (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The focus of this research is to describe the policy strategy carried out by Indonesia regarding China's domination and expansion in the Indo-Pacific. The rise of China which consists of economy and military, partnership, investment, and trade, changed the regional system and also created a revolution for other countries. Indonesia sees that China's economic power will affect its national interests in the future. That is why Indonesia must have a strong foreign policy and strategy to counter Chinese influence while remaining engaged and building a strong partnership with China. Due to this, Indonesia finally made a strategy to realize the AOIP (ASEAN Outlook on Indo Pacific) as a way to dispel China's dominance in the Indo-Pacific. This paper uses a Neoliberalism perspective that focuses on strategy theory, the level of analysis of the international system, and also the concept of national interest. Using strategy theory, this study aims to reveal Indonesia's strategy in realizing the AOIP (ASEAN Outlook on Indo Pacific). This study shows that the Indonesian government has a strong commitment to realizing AOIP through the mechanism of moving directly as an actor or through ASEAN with the concept of Centrality. This is based on Indonesia's interests to stem China's power with the Belt Road Initiative in the indo-Pacific region. Keywords: Strategy, AOIP, ASEAN Centrality.